Evaluation of the Indonesian Government Policy Regarding the Age of Freight Transport Vehicles (Trucking - Land Transportation) - Boy Hutabarat, Sunny; Munandar, Aries; Simarmata, Juliater (Journal of Accounting and Finance Management, 2025)
This study employs a SWOT analysis to evaluate the policy on age restrictions for freight vehicles in Indonesia. This method was chosen due to its ability to identify and analyze both internal and external factors that comprehensively influence policy implementation. Primary data were collected through in-depth interviews and focus group discussions (FGD) with key stakeholders, while secondary data were gathered from policy documents, statistical reports, and relevant scientific publications. The SWOT analysis involved evaluating internal factors (strengths and weaknesses) and external factors (opportunities and threats) impacting the policy, with weighting determined through expert judgment. The analysis revealed that PT XYZ is positioned in Quadrant III, indicating that the company faces more external threats than opportunities, although internal factors suggest adequate strengths. Recommended strategies include advocating for vehicle age restrictions, operational digitization, service diversification, and the implementation of sustainability efforts to improve competitiveness. The implementation of these strategies is expected to enhance efficiency, customer satisfaction, and corporate reputation. Collaboration with the government and logistics business associations will be crucial for successfully implementing these strategies to ensure sustainable growth.